Comparative study of toxic comments classification using machine learning algorithms - Razzak, Razia; Sadril, Md.; Shakil, Mahmudul Hasan; Rahman, Mahfuzur; Taki, Sabiha Tul Omman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.